1981
DOI: 10.1111/j.1600-0765.1981.tb00987.x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology of ligature‐induced periodontitis in the cynomolgus monkey

Abstract: The cultivable subgingival microflora in the cynomolgus monkey, Macaca fascicularis, was monitored during the ligature‐induced progression of naturally occurring gingivitis to periodontitis. Clinical and microbiological observations were divided into four stages. Stage I, prior to ligature placement, was characterized clinically by chronic generalized gingivitis and microbiologically by Gram‐positive cocci and rods with B. melaninogenicus ss. intermedius the dominant Gram‐negative organism. Stage II, 1 to 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 22 publications
9
122
0
1
Order By: Relevance
“…It was beyond the scope of this study to extend the routinely used tests for identification of these organisms since none of them showed a characteristic pattern or occurred frequently enough. With 37% Gram-negative anaerobic rods, 13% BPB in the control group and 19% in the test group at time 0 (Table I and II) the data in this report are comparable to stage IV desscribed by Kornman, Holt and Robertson (1981). But a separation of BPB into saccharolytic and asaccharolytic BPB reveals differences.…”
Section: Sampling Methodssupporting
confidence: 68%
“…It was beyond the scope of this study to extend the routinely used tests for identification of these organisms since none of them showed a characteristic pattern or occurred frequently enough. With 37% Gram-negative anaerobic rods, 13% BPB in the control group and 19% in the test group at time 0 (Table I and II) the data in this report are comparable to stage IV desscribed by Kornman, Holt and Robertson (1981). But a separation of BPB into saccharolytic and asaccharolytic BPB reveals differences.…”
Section: Sampling Methodssupporting
confidence: 68%
“…Thus, intervals suggested for histomorphometric analysis are 1, 3, and 6 mos (Giannobile et al, 1994). Limitations are that the defects are restricted to the interproximal region, the maintenance of nonhuman primates is expensive, and the establishment of periodontal lesions requires significant time (Kornman et al, 1981;Caton et al, 1994). This model has been used for evaluation of the efficacy of biologics and GTR barriers (Rutherford et al, 1992;Giannobile et al, 1994Giannobile et al, , 1996Kostopoulos and Karring, 2004).…”
Section: Ligature-induced Periodontal Lesions In Non-human Primatesmentioning
confidence: 99%
“…These animals also form microbial plaque and calculus in the periodontium; however, they rarely exhibit spontaneous progression of gingival inflammation to periodontal disease (Schou et al, 1993). Various approaches have been designed for the predictable induction of periodontal defects (Kornman et al, 1981;Brecx et al, 1985). Thus, given the great similarities in relation to tooth size, anatomy, and healing characteristic, non-human primates make for an appropriate model system for the evaluation of NMF.…”
Section: Non-human Primatesmentioning
confidence: 99%
“…This model also has permitted an assessment of the role of the emerging microbiota and the immune response to selected members of this microbiota to either protect against disease progression or to exacerbate the inflammatory process during the longitudinal progression of the inflammatory disease (18)(19)(20). We and others have shown that characteristics of the innate and humoral immune responses and the destruction of bone and connective tissue that accompany naturally occurring and ligature-induced periodontitis in Macaca fascicularis, Saimiri sciureus, Macaca nemestrina, Macaca mulatta, and Papio anubis parallel those observed in human periodontitis (5,6,(21)(22)(23).…”
mentioning
confidence: 99%